Methods of prolonging the effect of caudal block in children - Xu, Weiyi; Wei, Haixu; Zhang, Tao (Frontiers in Pediatrics, 2024)
Caudal epidural blockade is one of the most frequently administered regional anesthesia techniques in children. It is a supplement during general anesthesia and for providing postoperative analgesia in pediatrics for sub-umbilical surgeries, especially for genitourinary surgeries. However, the duration of the analgesic effect is occasionally unsatisfactory. In this review, we discuss the main advantages and disadvantages of different techniques to prolong postoperative analgesia for single-injection caudal blockade in children. A literature search of the keywords “caudal”, “analgesia”, “pediatric”, and “children” was performed using PubMed and Web of Science databases. We highlight that analgesic quality correlates substantially with the local anesthetic's type, dose, the timing relationship between caudal block and surgery, caudal catheterization, and administration of epidural opioids or other adjuvant drugs.